Analisis Pengaruh Terapi Jus Jambu Biji dan Madu dalam Menurunkan Frekuensi Buang Air Besar pada Anak Pra Sekolah (Usia 4-5 Tahun) yang Mengalami Diare Akut - octo zulkarnain; HERI NUR CAHYANTO (Jurnal Penelitian Keperawatan Kontemporer, 2022)
Background: Diarrhea remains a global issue with high rates of morbidity and mortality in many countries, especially in developing nations, and it is a major cause of illness and death among children worldwide. Objective: This study aims to investigate the effect of guava seed and honey therapy on reducing the frequency of defecation in pre-school children (aged 4-5 years) with acute diarrhea. Methods: The research method used in this study was pre-experimental with a pre-post test group design. The study population consisted of 26 pre-school children aged 4-5 years who experienced acute diarrhea, selected using total sampling technique. Data were collected using a questionnaire, and data analysis was performed using the Wilcoxon test with a significance level of 0.05. Results: The results of the study showed that before being given guava seed and honey therapy, the frequency of defecation in all children was in the high category, i.e., more than 2 times a day (100%). After receiving guava seed and honey therapy, the majority of children experienced a reduction in the frequency of defecation, with 17 respondents (65.4%), while a small portion still had a high frequency of defecation, with 9 respondents (34.6%). The results of the analysis showed P=0.000. Conclusion: Based on the research findings, it can be concluded that the administration of guava seed and honey therapy has an effect on reducing the frequency of defecation in pre-school children (aged 4-5 years) with acute diarrhea. Keywords: Guava seed and honey therapy, Diarrhea, Pre-school children